Kosmotelegensia Akal Manusia dalam al-Qur’an dan Implikasinya terhadap Kecerdasan Buatan (AI) - Nur Ilmi; Halimah Basri; Muhsin Mahfudz (At-Tadris: Journal of Islamic Education, 2026)
This study aims to analyze the concept of human intellect in the Qur’an, formulate the concept of cosmotelegence as a Qur’anic paradigm, and examine its implications for the development of Artificial Intelligence (AI). The research employed a qualitative approach using the maudhu’i (thematic) interpretation method and Qur’anic epistemology through library research. Data were collected from Qur’anic verses concerning human intellect and the interpretations of classical, modern, and contemporary exegetes, particularly Ibn Kathir, Al-Maraghi, and M. Quraish Shihab. The findings reveal that the Qur’an presents intellect not merely as the capacity for reasoning but as an intellectual process encompassing reflection, understanding, moral awareness, and spiritual responsibility. Based on these findings, the study formulates the concept of cosmotelegence, which integrates revelation, human reason, and the realities of life. This concept emphasizes that true intelligence is directed not only toward acquiring knowledge but also toward cultivating morality and promoting the common good. Its implications for AI include strengthening a benefit-oriented AI development paradigm, reinforcing ethical principles based on Qur’anic values, and affirming humans as moral agents responsible for decision-making. Therefore, cosmotelegence offers a relevant Qur’anic framework for fostering a technologically advanced digital civilization grounded in moral, spiritual, and humanitarian values.